THE MAIN EFFECTS OF THE DRUG ADAPTOL - Ergashov Bekhruzjon Komilovich (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Adaptol is a unique drug in many ways, practically has no analogues either from pharmacological or clinical pharmacotherapeutic points of view. At the same time, the need in drugs of precisely this type of action, such as Adaptol, in modern medical practice is steadily increasing. Let's try to analyze what is unique about this drug and its relevance for today stage of development of medicine. Adaptol has a complex effect on the body, multilateral impact, in which the leading its neurotropic properties play a role. Actively penetrating the blood-brain barrier, Adaptol affects various structural and functional elements of neurons, mainly the hypothalamus and limbic system.